2016
DOI: 10.7589/52.2s.s40
|View full text |Cite
|
Sign up to set email alerts
|

LEUKOCYTE COPING CAPACITY AS A TOOL TO ASSESS CAPTURE- AND HANDLING-INDUCED STRESS IN SCANDINAVIAN BROWN BEARS (URSUS ARCTOS)

Abstract: PREFACECompilation of this document was initiated by the Norwegian Directorate for Nature Management in order to establish recommended protocols for capture, chemical immobilization, anesthesia and radiotagging of free-ranging brown bears (Ursus arctos), gray wolves (Canis lupus), wolverines (Gulo gulo) and Eurasian lynx (Lynx lynx). In addition, procedures to ensure proper sampling of biological materials for management, research and banking purposes have been included.The current protocols are based on nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 59 publications
(59 reference statements)
3
17
0
Order By: Relevance
“…We attribute this lack of correlation to a large individual variation in how animals cope with a stressful situation behaviorally and physiologically [15, 69, 70], impeding the detection of quantitative effects of a stressor, at least at low sample sizes like they are commonly faced in field studies. Moreover, our results are supported by the findings of Esteruelas et al [32] showing that LCC levels did not correlate with heart rate, N:L ratio nor cortisol concentrations in Scandinavian brown bears. It should be noted, however, that those animals were anesthetized, resulting in additional physiological alterations.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We attribute this lack of correlation to a large individual variation in how animals cope with a stressful situation behaviorally and physiologically [15, 69, 70], impeding the detection of quantitative effects of a stressor, at least at low sample sizes like they are commonly faced in field studies. Moreover, our results are supported by the findings of Esteruelas et al [32] showing that LCC levels did not correlate with heart rate, N:L ratio nor cortisol concentrations in Scandinavian brown bears. It should be noted, however, that those animals were anesthetized, resulting in additional physiological alterations.…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted, however, that those animals were anesthetized, resulting in additional physiological alterations. As in our findings, the classical parameters measured by Esteruelas et al [32] indicated that animals were certainly stressed, but likewise did not allow for quantifying stress responses [61]. This, however, is apparently not the case for the LCC.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Several authors have previously indicated the need for a common language to unite conservation and animal welfare sciences and have attempted to identify common metrics to do so and to more clearly delineate the point at which biological fitness and welfare converge. “Stress” was proposed as that unifying concept, and measurements of stress have been widely used to evaluate the fitness and welfare impacts of human-generated conditions and procedures on animals of wild species [e.g., ( 42 , 75 , 78 , 91 , 92 , 94 , 155 , 156 )]. Stress has usually been characterized according to physiological responses, primarily activation of the hypothalamic-pituitary-adrenal (HPA) axis elicited by external threats or disruptions to internal conditions, i.e., homeostasis ( 157 , 158 ).…”
Section: Conception Of Animal Welfare Influences Its Evaluation and Ementioning
confidence: 99%